2018
DOI: 10.4103/jcd.jcd_154_17
|View full text |Cite
|
Sign up to set email alerts
|

Apical dye leakage of two single-cone root canal core materials (hydrophilic core material and gutta-percha) sealed by different types of endodontic sealers: An in vitro study

Abstract: Aim of the Study:The aim of this study was to compare the apical sealing ability of two single-cone filling materials when sealed with different types of root canal sealers.Materials and Methods:Eighty extracted maxillary and mandibular canines were selected and their crowns were cut. The root canals were prepared using ProTaper Universal rotary system until size F4 and then divided into seven experimental groups (n = 10 each) and two control groups (n = 5 each). Samples of Groups 1, 2, and 3 were filled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, their tabulation and reconfirmation of the results were unclear and sample size for each group was small ( n = 10). As a separate note, El Sayed et al [ 40 ] reported the lowest apical leakage value with the CSBs, however there was no significant difference when compared with the RBS. High solubility of CSBs might raise questions on the long-term sealing ability [ 62 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, their tabulation and reconfirmation of the results were unclear and sample size for each group was small ( n = 10). As a separate note, El Sayed et al [ 40 ] reported the lowest apical leakage value with the CSBs, however there was no significant difference when compared with the RBS. High solubility of CSBs might raise questions on the long-term sealing ability [ 62 ].…”
Section: Discussionmentioning
confidence: 95%
“…The main characteristics of the included studies are shown in Table 3 . Ten studies on the adaptation to root canal walls were included [ 30 , 31 , 32 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In comparison to the RBS, CSBs showed similar values of void volume marginal adaptation in five studies [ 32 , 36 , 37 , 38 , 39 ] whilst at the apical, mid, and coronal thirds, these values were high in three studies [ 31 , 35 , 41 ] and low in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study evaluating apical sealing ability using apical linear dye penetration and comparing AH Plus ® , Endosequence BC ® Sealer™, and MTA Fillapex ® showed the lowest apical leakage value for the SC technique used with the EndoSequence BC ® Sealer™ [ 98 ]. As already shown in the literature, results for the dye techniques remain contradictory, inducing a wide variability.…”
Section: Reviewmentioning
confidence: 99%
“…Numerous in-vitro and in-vivo investigations present inconsistent and ambiguous results about the proper selection of sealers, ultimately deciding the treatment outcome. Epoxy resin-based sealers 12 , 13 and bioceramic sealers 14 , 15 , 16 , 17 were typically suggested in the investigations on different sealers. Assimilation of all available information from the literature on these materials can assist the practitioner in executing void-free endodontic therapy.…”
Section: Introductionmentioning
confidence: 99%